CD4+CD25+LAG3+ T Cells With a Feature of Th17 Cells Associated With Systemic Lupus Erythematosus Disease Activity - Kato, Rika; Sumitomo, Shuji; Tsuchida, Yumi; Tsuchiya, Haruka; Nakachi, Shinichiro; Sakurai, Keiichi; Hanata, Norio; Nagafuchi, Yasuo; Kubo, Kanae; Tateishi, Shoko; Kanda, Hiroko; Okamura, Tomohisa; et al. (Frontiers in Immunology, 2019)
Systemic lupus erythematosus (SLE) is an autoimmune disease that involves multiple immune cell subsets. We analyzed immune cell subsets in human peripheral blood mononuclear cells (PBMC) in order to identify the cells that are significantly associated with SLE disease activity and treatment. The frequencies of various subsets of CD4+ T cells, B cells, monocytes and NK cells in PBMC were assessed in 30 healthy controls (HC), 30 rheumatoid arthritis (RA) patients and 26 SLE patients using flow cytometry. The correlations between subset frequencies in SLE and clinical traits including Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) were examined. Changes in subset frequencies after the treatment in SLE patients were investigated. We focused on CD25+LAG3+ T cells and investigated their characteristics, including cytokine secretion, mRNA expression and suppression capacity. We assessed correlations between CD25+LAG3+ T cells and SLEDAI by Spearman's rank correlation coefficient. CD25+LAG3+ T cells were significantly increased in SLE whereas there were few in RA and HC groups. CD25+LAG3+ T cell frequencies were significantly correlated with SLEDAI and were increased in patients with a high SLEDAI score (> 10). CD25+LAG3+ T cells produced both IL-17 and FOXP3, expressed mRNA of both FOXP3 and RORC and lacked suppressive capacity. CD25+LAG3+ T cells were associated with disease activity of SLE. CD25+LAG3+ T cells had features of both CD25+FOXP3+ regulatory T cells (CD25+ Treg) and Th17. CD25+LAG3+ T cells could be associated with the inflammatory pathophysiology of SLE.